Competence-Oriented Technology for Long-Term Athletic Development of Young Ice Hockey Players - Sukhachev, E. A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to theoretically substantiate and practically develop a competence-based technology for the long-term sports training of young ice hockey players aged 7–17, ensuring the alignment of goals, content, methods, and performance criteria within the system of long-term athletic development. Methods and structure of the study. The research relies on systemic, activity-based, competence-based, and synergetic methodological approaches. Theoretical methods included analysis, modeling, structural-functional and comparative analysis. Empirical methods comprised pedagogical observation, testing, surveys, and experimental design (ascertaining, formative, and local stages). Instrumental methods included heart rate monitoring, electromyography, heart rate variability analysis, psychophysiological testing, and video analysis of competitive activity. The study involved approximately 2,420 male ice hockey players aged 7–17 and over 50 coaches representing sports schools and club systems implementing the National Ice Hockey Training Program. The experimental work was carried out between 2010 and 2025. Results and conclusions. For the first time, a competence-based technology for the training of young ice hockey players has been theoretically substantiated and developed, including target, content, procedural, and evaluation modules. The “competence architecture” was identified, reflecting the systemic interrelation of physical, technical, tactical, cognitive, and personal-regulatory components of athlete readiness. A system of criteria and indicators for competence assessment was developed, ensuring pedagogical feedback and manageability of the long-term process. Experimental data confirmed that the implementation of the competence-based technology increases integrative readiness, improves competitive performance, decision-making speed, stability, and teamwork effectiveness among young hockey players. The competence-based training technology for young hockey players serves as an effective tool for integrating training, competitive, educational, and developmental processes into a unified system. Its implementation ensures individualization, continuity, and manageability of long-term sports development while fostering athletes’ ability to perform effectively in dynamic and uncertain competitive environments.